Effects of Different Strain Rates on the Impact Properties of Recycled Aggregate Concrete Modified With Nanosilica Solution and Polyvinyl Alcohol Fiber - Wang, Xingguo; Jiang, Maolin; Zhang, Xianggang; Cheng, Zhaoxia; Gong, Jian; Cheng, Fei (Frontiers in Materials, 2021)
The recycled coarse aggregate(RA) was modified by 2% nanosilica solution, and the split Hopkinson pressure bar (SHPB) test device was used to study the dynamic impact properties of modified recycled aggregate concrete(RAC) mixed with polyvinyl alcohol (PVA) fibers. RA replacement percentage, the amount of PVA fiber and the strain rate were variable. The failure pattern, stress-strain curve of nanosilica solution and PVA fiber modified RAC were given under different strain rate conditions. Dynamic peak stress, peak strain and dynamic increase factor (DIF) of the specimens are discussed. The results show that the stress and dynamic peak strain value of the specimen increase with the increase of strain rate; Moreover, with the increasing of RA replacement percentage and PVA fiber content, the dynamic peak stress of the specimen decreases, while the dynamic peak strain and DIF value increase. The incorporation of nanosilica modified RA is beneficial to the improvement of the impact performance of RAC, and the incorporation of an appropriate amount of PVA fiber effectively improves the deformability of RAC.